Nothobranchius elucens, a new species of seasonal killifish from the upper Nile drainage in Uganda (Cyprinodontiformes: Nothobranchiidae) - Nagy, Béla (Zootaxa, 2021)
Nothobranchius elucens, new species, from a seasonal habitat in the Aringa system of the Achwa River in the upper Nile drainage in northern Uganda, is described. It belongs to the N. rubroreticulatus species group, whose members are characterised by male coloration of anal and caudal fins with slender light blue subdistal band and slender dark distal band. Nothobranchius elucens is distinguished from all other members of the genus by the following characters in males: body colouration golden-grey with brown scale margins creating irregular vertical stripes on trunk; anal fin yellow with brown spots proximally, with slender brown median band, followed by a slender light blue subdistal band and a slender black distal band; caudal fin brown proximally and medially, followed by a slender light blue subdistal band and a slender black distal band; dorsal fin golden with irregular brown stripes and narrow light blue subdistal band and with narrow black distal band. Furthermore, it differs from the closest known relative, N. taiti, also by the morphometric characters of having a smaller head length of 29.5–33.1 % SL; smaller prepectoral length of 31.2–33.9 % SL; greater head depth of 81–87 % HL; greater interorbital width of 43–49 % HL; and greater caudal peduncle length of 145–152 in % of its depth.